Peran Soft Skills dalam Memediasi Pengaruh Pengenalan Lapangan Persekolahan (PLP), Minat Menjadi Guru dan Lingkungan Keluarga terhadap Kesiapan Mahasiswa Menjadi Guru pada Program Studi Pendidikan Administrasi Perkantoran FEB UNNES - Kristiani, Tria; Tusyanah, Tusyanah (Universitas Negeri Semarang, 2024)
The aim of this research is to examine the role of soft skills in mediating the influence of introduction to the school field (PLP), interest in becoming a teacher and family environment on students' readiness to become teachers. The type of research used is quantitative. Data was collected using a questionnaire and analyzed using SEM-PLS. The population in this study was 107 students from the FEB UNNES office administration study program in 2020. The sample was 85 students determined using the Slovin formula. The research results showed that of the 10 (ten) hypotheses proposed, there were 8 (eight) hypotheses accepted and 2 (two) hypotheses rejected, with the following details, PLP has a positive and significant effect on readiness to become a teacher, PLP has a positive and significant effect on soft skills, interest has a positive and significant effect on readiness to become a teacher, interest has a positive and significant effect on soft skills, family environment has a positive and significant effect on readiness to become a teacher, family environment has a positive and significant effect on soft skills, soft skills have a positive and significant effect on readiness to become a teacher, interest mediated by soft skills has a positive and significant effect on readiness to become a teacher. Furthermore, PLP mediated by soft skills has a positive but not significant effect on readiness to become a teacher, likewise the family environment mediated by soft skills also has a positive but not significant effect on readiness to become a teacher